Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1029/2008ja013448
|View full text |Cite
|
Sign up to set email alerts
|

Observations of GW/TID oscillations in the F2 layer at low latitude during high and low solar activity, geomagnetic quiet and disturbed periods

Abstract: Ionospheric vertical sounding observations, using a digital ionosonde, are being carried out on a routine basis at Sao Jose dos Campos (23.2°S, 45.9°W; dip latitude 17.6°S, hereafter referred to as SJC), Brazil, located under the southern crest of the equatorial ionization anomaly (EIA), since August 2000. In this paper, we present and discuss the seasonal variation of gravity wave (GW) and traveling ionospheric disturbance (TID) oscillations in the ionospheric F2 layer during high solar activity (HSA, Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 35 publications
(68 reference statements)
10
50
0
Order By: Relevance
“…3a and d), and the corresponding parameters (T , V z , and λ z ) are in agreement with those found by Klausner et al (2009). The UT of such signatures suggests that for these cases GWs are excited by the solar terminator passage (Somsikov and Ganguly, 1995;Galushko et al, 1998).…”
Section: Discussion and Summarysupporting
confidence: 76%
See 2 more Smart Citations
“…3a and d), and the corresponding parameters (T , V z , and λ z ) are in agreement with those found by Klausner et al (2009). The UT of such signatures suggests that for these cases GWs are excited by the solar terminator passage (Somsikov and Ganguly, 1995;Galushko et al, 1998).…”
Section: Discussion and Summarysupporting
confidence: 76%
“…However, the most important thing to note in Table 1 is that all the RSF signatures appear well after the local sunset, which in this month occurs on average at 19:00 local time (LT=UT−4), and also well after the time an EPB, that was formed at sunset at the dip equator, takes to drift to the EA, ∼95 min as illustrated in a very comprehensive way by Whalen (2000). This suggests the two following considerations: 1) the observed RSF do not seem to be signature of EPBs generated around sunset at the magnetic equator; instead they may be considered signatures of plasma instabilities that were locally generated; 2) the PSSR, that can extend under the southern crest of the EA as was shown by Klausner et al (2009) and by Abdu et al (2009), cannot be considered itself as the only cause of RSF appearance on the ionogram, and a triggering process associated with PSSR is needed to cause instabilities responsible for RSF development. In support of this argument, Fig.…”
Section: Analysis and Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…6 and 9). In fact, in these cases STs are due to corrugation in the isodensity surfaces caused by GW propagation which, in turn, can be considered to be the mechanism that, amplifying the post sunset seeding sources of irregularities (Fejer et al, 1999;Hysell and Burcham, 2002;Klausner et al, 2009), gives rise to the instabilities responsible for the RSF signatures occurring on the ionogram. On the other hand, under the southern crest of the EIA and for medium-low solar activity, also Fagundes et al (2009) andCandido et al (2011) have recently found evidence that spread-F events can be caused by ionospheric disturbances that are unrelated to equatorial processes, suggesting that traveling ionospheric disturbances and TPWIDs might be one of the main sources of these non-equatorial phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…These waves are strongly connected with the ionospheric day-to-day variability in the equatorial and low latitudes and are important topics of investigation. Considerable research has gone into understanding the physics behind the observed high variability, particularly in the F2 layer [Fagundes et al, 2005Klausner et al, 2009;MacDougall et al, 2009;Rishbeth et al, 2009]. For many years, it was thought that during geomagnetic quiet conditions, the equatorial and low-latitude F2 layer was mainly perturbed by waves or electric fields generated by the equatorial electroject (EEJ), via tidal winds, which are transmitted along the magnetic field lines to equatorial F-region altitudes .…”
Section: Introductionmentioning
confidence: 99%